Tren Integrasi Literasi Ekologis dalam Materi Pembelajaran Bahasa Indonesia dalam Kurikulum 2013 dan Kurikulum Merdeka - Zilfania Qathrun Nada; Heni Listiana (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2024)
This study discusses the importance of ecological literacy in increasing students' awareness of the environment through learning Indonesian. This study aims to combine ecological literacy in Indonesian language materials in junior high schools and senior high schools in the 2013 Curriculum and the Independent Curriculum, and to assess the effectiveness of the learning methods used by teachers. The study used a qualitative approach through analysis of curriculum content, learning materials, and interviews with Indonesian language teachers. The analysis also includes a study of literary works that raise environmental themes. The results show that the 2013 Curriculum emphasizes more on introducing the environment through narrative and informative texts, while the Independent Curriculum focuses more on direct student involvement through observation and real action activities. Both are effective in increasing students' environmental awareness, although with different approaches. In conclusion, the 2013 Curriculum focuses on theoretical understanding, while the Independent Curriculum encourages real action for environmental conservation.